2023
DOI: 10.33003/fjs-2023-0702-1472
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Drinking Water Quality Monitoring in the Northern Part of Nigeria: A Catalyst to Achieving Sustainable Development Goals

Abstract: Access to clean water for drinking and domestic activities remains a critical issue in Nigeria, especially in the northern region. The increasing global population and importance of water for life have led to a quantitative and qualitative increase in its demand. This paper reports a comprehensive review of the quality of water sources utilized for consumption in northern Nigeria over the last decade. The report aims to serve as a reference point to assess the possibility of achieving Sustainable Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, the Federal Ministry of Water Resources (FMWR), in its 2022 report of findings on water sanitation and hygiene, documented that almost 87% (179 million) of Nigerians lack access to a clean water supply, with the north mainly affected (FMWR, NBS, UNICEF, 2022). Similarly, a recent study investigating the progress of drinking water quality in northern Nigeria found that more than half (55.74%) of the water sources were unfit for consumption (Imam et al, 2023). Therefore, the need for regular monitoring of water quality, driven by empirical evidence on the water quality, particularly HM content, considering the numerous evidence of its potential chronic health impacts on consumers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Federal Ministry of Water Resources (FMWR), in its 2022 report of findings on water sanitation and hygiene, documented that almost 87% (179 million) of Nigerians lack access to a clean water supply, with the north mainly affected (FMWR, NBS, UNICEF, 2022). Similarly, a recent study investigating the progress of drinking water quality in northern Nigeria found that more than half (55.74%) of the water sources were unfit for consumption (Imam et al, 2023). Therefore, the need for regular monitoring of water quality, driven by empirical evidence on the water quality, particularly HM content, considering the numerous evidence of its potential chronic health impacts on consumers.…”
Section: Introductionmentioning
confidence: 99%